Activité antibactérienne des feuilles d’extrait de la Moringa oleifera - Bouhalima, asma; Beressa, zohra (My University, 2021)
Our work aims to know the evaluation of the antibacterial effects of extract of Moringa oleifera leaves vis-à-vis six pathogenic strains tested: Staphylococcus aureus ATCC 33862, Klebsiella pneumoniae ATTC 13883, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 , Salmonella paratyphi A and a fungus Candida albicans ATCC 10231, by well diffusion method on AWDT agar and Minimum Inhibitory Concentration (MIC). AWDT test results revealed the following diameters in descending order, with Staphylococcus aureus ATCC 33862 (diameter of inhibition zone = 22 mm), Escherichia coli ATCC 25922 (diameter of inhibition zone = 14 mm) , Klebsiella pneumoniae ATTC 13883 (diameter of the zone of inhibition = 12 mm). The evolution of this antibacterial effect shows that the most interesting zone of inhibition is noted by the strain Staphylococcus aureus ATCC 33862. No antimicrobial activity was noted against the pathogenic strains Pseudomonas aeruginosa ATCC27853, Salmonella paratyphi A and Candida albicans ATCC 10231. The highest MIC recorded values are 70 μg / mg for Staphylococcus aureus ATCC 33862, while the lowest MIC recorded is 21 μg / ml for Klebsiella pneumoniae ATTC 13883.
Keywords: Moringa oleifera - Antimicrobial activity - pathogenic strains.